2000
DOI: 10.1093/ajcn/72.6.1535
|View full text |Cite
|
Sign up to set email alerts
|

Primed, constant infusion with [2H3]serine allows in vivo kinetic measurement of serine turnover, homocysteine remethylation, and transsulfuration processes in human one-carbon metabolism

Abstract: The appearance of both [(2)H(1)]- and [(2)H(2)]methionine forms indicates that both cytosolic and mitochondrial metabolism of exogenous serine generates carbon units in vivo for methyl group production and homocysteine remethylation. This study also showed the utility of serine infusion and indicated functional roles of cytosolic and mitochondrial compartments in one-carbon metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 28 publications
6
59
0
Order By: Relevance
“…Both purine synthesis and oxidative release of carbon dioxide and THF by 10-formyl-THF dehydrogenase (EC 1.5.1.6) draw on the 10-formyl-THF pool. The irreversible and nonproductive dissipation of an excess in transferable one-carbon units is likely to be a significant regulatory factor, because the intrahepatic concentration of 10-formyl-THF exceeds the half-maximal equilibrium constant K m of 10-formyl-THF dehydrogenase (40). The 10-formyl-THF synthase activity of C-1-THF synthase, on the other hand, can add to the 5,10-methylene-THF pool by linking formate to free folate.…”
Section: Discussionmentioning
confidence: 99%
“…Both purine synthesis and oxidative release of carbon dioxide and THF by 10-formyl-THF dehydrogenase (EC 1.5.1.6) draw on the 10-formyl-THF pool. The irreversible and nonproductive dissipation of an excess in transferable one-carbon units is likely to be a significant regulatory factor, because the intrahepatic concentration of 10-formyl-THF exceeds the half-maximal equilibrium constant K m of 10-formyl-THF dehydrogenase (40). The 10-formyl-THF synthase activity of C-1-THF synthase, on the other hand, can add to the 5,10-methylene-THF pool by linking formate to free folate.…”
Section: Discussionmentioning
confidence: 99%
“…An elegant stable isotope study in humans (55) provides further support for the role of mitochondrial one-carbon units in the remethylation of homocysteine. Gregory et al (55) showed that both cytoplasmic and mitochondrial one-carbon units end up in the methyl group of methionine following infusion of deuterated serine. This result strongly supports mitochondrial formate production as a significant contributor to cytoplasmic one-carbon units in vivo in mammals and places the mitochondrial C 1 -THF synthase in the center of this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria contain a substantial portion of the cellular folate and some of the enzymes of the central cycle, namely SHMT, MTD, MTCH, FTD, and FTS (13,26). It is generally thought that mitochondria import serine from and export formate to the cytoplasm (18,38,90). Our basic model should be thought of as summing the folate cycles of cytoplasm and mitochondria.…”
Section: Folate-enzyme Binding and Homeostasismentioning
confidence: 99%